Bolivia: AOPEB Information Centres - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The AOPEB Information Centres form a network of specialised information centres now offer farmers online access to information on production methods and a virtual marketplace for products such as cocoa and coffee.